(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2009)
Sixty-three conodont species and subspecies from the Kal-e-Sardar section indicate that the strata span early to late Famennian. Contrary to most of the sections measured in the Shishtu Formation, the icriodid-polygnathid biofacies is restricted to the lower part of Kal-e-Sardar Famennian succession. Palmatolepid and bispathodid-dominated biofacies in the middle and upper part of section represent a deep shelf to mid-continental slope marine environment. The currently accepted ranges of P. tichonovitchi, P. tenellus and P. inconcinnus are early Famennian, late Frasnian-early Famennian, and early to middle Famennian, respectively, together with middle to late Famennian for P. nodoundatus. Two new species, Polygnathus sardarensis and P. yazdii, are proposed.